PARTISIPASI PETANI JAGUNG TERHADAP PROGRAM TATA AIR MIKRO (TAM) DI DESA SUMBER MAKMUR, KECAMATAN LUBUK PINANG, KABUPATEN MUKOMUKO - Riyadi, Slamet; Nabiu, Musriyadi; Yulianti, Ellys (Jurnal AGRISEP, 2012)
The objectives of this study are to measure participation level of corn farmers to Micro Water Management (TAM) and what factors are associated with it. The number of samples taken in this study is 60 people from the peasant population of 145 people from six farmer groups. Furthermore, of the 60 people determined proportionately from each farmer groups. To determine the relationships between the independent variables with the dependent variable used Non Parametric Statistical analysis of Spearman rank correlation. The research showed that the level of participation in the activities of corn farmer to the Micro Water Management (TAM) in the Sumber Makmur village in the high category. Formal education factors has a real connection with the level of participation, while the land area, family income level and perception has no real relationship with the level of participation in the activities of corn farmers to the Micro Water Management (TAM) in the Sumber Makmur village.